2020
DOI: 10.21203/rs.2.21715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations among Cognitive Functions, Plasma DNA, and Diffusion tensor image along the perivascular space (DTI-ALPS) in Patients with Parkinson's Disease

Abstract: Background Parkinson’s disease (PD) is a common neurodegenerative disease associated with accumulation of misfolding proteins and increased neuroinflammation. The purpose of this study was to utilize diffusion tensor image analysis along the perivascular space (DTI-ALPS) to evaluate glymphatic system activity, and its relationship with systemic oxidative stress status in PD patients. Methods Magnetic resonance imaging and neuropsychological tests were conducted on 25 PD patients with normal cognition (PDN), 25… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The DTI-ALPS method is used for evaluating the glymphatic system's function or the interstitial fluid dynamics, and this method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. One of the report showed that results of ALPS method were significantly related to glymphatic clearance function calculated on MRI by intrathecal administration of GBCA [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DTI-ALPS method is used for evaluating the glymphatic system's function or the interstitial fluid dynamics, and this method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. One of the report showed that results of ALPS method were significantly related to glymphatic clearance function calculated on MRI by intrathecal administration of GBCA [28].…”
Section: Discussionmentioning
confidence: 99%
“…The DTI-ALPS method provides ALPS index, which is a ratio of the diffusivity in the direction of the perivascular space and the diffusivity in the direction perpendicular to both major fiber tract and perivascular space, based on a special spatial relationship in the fiber tracts and the perivascular space in the axial imaging plane at the corona radiata [19,20]. Recently, the DTI-ALPS method has been adopted in several studies evaluating the alteration of the glymphatic system or interstitial fluid dynamics in various pathologies [21][22][23][24][25][26][27][28]. These reports indicated that the ALPS-index is a useful biomarker to evaluate the interstitial fluid dynamics or glymphatic function.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, enlarged perivascular space (EPVS) is reported to be caused by metabolic waste obstruction, serving as an additional index for assessing glymphatic function [10]. Using the DTI-ALPS method, previous researchers have identified the role of glymphatic dysfunction in PD at different stages [11][12][13][14][15][16][17][18][19], as well as patients with isolated eye movement behavior disorder (RBD) [18,20]. They have also reported correlations between DTI-ALPS and cognitive function [11], as well as motor performance [11,21,22].…”
Section: Introductionmentioning
confidence: 99%